Forensic Linguistic Analysis of South Korean Artist Jang Ja–Yeon Suicide Letter - Riska Safitri; Suhardi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
This research seeks to investigate Jang Ja-yeon's suicide note. The focus of this research is the suicide letter written by Jang Ja-yeon. This study employs a descriptive a qualitative approach. The data collecting technique used is to use the procedure of observing, recording and analyzing it using the equivalent method with the sorting process and then describing it. The data source in this research is Tribun News. The data in this study is Jang Ja-yeon's suicide note. The results in this study are to show that the letters are not relevant with Jang Ja Yeon's real handwritings. Grammatical errors go hand in hand with those written by Jun in her personal letters. Jang Ja Yeon's death case will also be investigated again.